Analysis of Physical Fitness Levels of High School Students Using the Indonesian Student Fitness Test Application (TKPN) - Muhammad Syifa’ Andiansyah; Muchamad Arif Al Ardha; Hamdani Hamdani; Nur Ahmad Arief (International Journal of Mechanical, Electrical and Civil Engineering, 2024)
Physical fitness is a person's ability to do something or a task well without excessive fatigue and can be useful in developing students' learning and insight. Apart from that, physical fitness is also important in learning, especially in learning PJOK. However, many people consider physical fitness unimportant. The aim of this research is to determine the level of physical fitness of students and the differences in physical fitness levels of vocational science and vocational social science at SMA Hang Tuah 5 Sidoarjo. This research involved class XI F2 and class XI F5. Class XI F2 has 33 students with a ratio of 17 male students and 16 female students. Class XI F5 has 36 students with a ratio of 19 male students and 17 female students. This research applies a non-experimental method with a comparative design using the Independent sample t-test data analysis technique. The TKPN test (Indonesian Student Fitness Test) was used as an instrument for this research. The results obtained from the SPSS application showed a hypothesis test value of 0.15 (p-value > 0.05), indicating that there was no difference in physical fitness. Meanwhile, from the norm results for fitness results in the TKPN test (Indonesian Student Fitness Test) there was a difference in scores of 4.47 for science vocational students in the very good category and 3.78 social science vocational students in the good category.